Pituitary cell differentiation from stem cells and other cells: toward restorative therapy for hypopituitarism?. (July 2014) - Willems, Christophe; Vankelecom, Hugo
The pituitary gland, key regulator of our endocrine system, produces multiple hormones that steer essential physiological processes. Hence, deficient pituitary function (hypopituitarism) leads to severe disorders. Hypopituitarism can be caused by defective embryonic development, or by damage through tumor growth/resection and traumatic brain injury. Lifelong hormone replacement is needed but associated with significant side effects. It would be more desirable to restore pituitary tissue and function. Recently, we showed that the adult (mouse) pituitary holds regenerative capacity in which local stem cells are involved. Repair of deficient pituitary may therefore be achieved by activating these resident stem cells. Alternatively, pituitary dysfunction may be mended by cell (replacement) therapy. The hormonal cells to be transplanted could be obtained by (trans-)differentiating various kinds of stem cells or other cells. Here, we summarize the studies on pituitary cell regeneration and on (trans-)differentiation toward hormonal cells, and speculate on restorative therapies for pituitary deficiency.